2008
DOI: 10.5739/isfp.2008.341
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Measurement of Tribological Parts in Swash-Plate Type Axial Piston Pumps

Abstract: Temperatures of a swash plate, cylinder block, and a valve plate of swash-plate type axial piston pumps with a rotating cylinder block and a rotating swash plate were measured. Thermocouples were embedded underneath these parts . Hydraulic mineral oils with ISO VG22, 32, 46, and 68 and a water-glycol type hydraulic fluid with VG32 were used as test fluids. The maximum discharge pressure was 20 MPa and the maximum rotational speed was 28.3 rps. The inlet oil temperatures were specified as 293-313 K. At the atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Many other researchers used the type (b) set up, as it recreates a quiet realistic test environment to evaluate slipper performance mainly by measuring friction and leakage [8][9][10][11]. The stationary slippers allow for interesting sensor placement for example temperature [12,13], pressure [10] or displacement sensors to measure the micro movement and gap height [14][15][16].…”
Section: State Of the Artmentioning
confidence: 99%
“…Many other researchers used the type (b) set up, as it recreates a quiet realistic test environment to evaluate slipper performance mainly by measuring friction and leakage [8][9][10][11]. The stationary slippers allow for interesting sensor placement for example temperature [12,13], pressure [10] or displacement sensors to measure the micro movement and gap height [14][15][16].…”
Section: State Of the Artmentioning
confidence: 99%
“…As most of these empirical studies were not performed in an actual pump environment, efficiency tests were infeasible. In the past two decades sensors and electronics have allowed for a less invasive measurement of both gap height and temperature in fully functional pumps [9]- [11], [24], [25], [29]- [32]. However, the findings mostly focused on the validation of simulation models, rather than a pump analysis.…”
Section: Literaturementioning
confidence: 99%
“…To validate the predicted temperature-efficiency trends, it is necessary to measure the cylinder block temperature in a regular pump setting, without modifying crucial pump components, as has been done in the past [9], [29], [38]. To accomplish this, a special telemetric system was used, which can accurately measure a large number of sensors simultaneously.…”
Section: Measurementmentioning
confidence: 99%
“…The experimental and theoretical results showed that the extrusion pressure and hot wedge support force were the main factors affecting the oil film thickness and bearing capacity, and the ideal slipper radius ratio and hole length-diameter ratio were obtained by optimizing the structural parameters of the slipper and oil composition. Kazama et al [21] took hydraulic oils with different viscosities and water-glycol hydraulic oil as test fluids and measured the temperatures of the swash plate, valve plate, and cylinder block by a thermocouple under different inlet oil temperatures and viscosities. The test results show that the temperature of the valve plate proportionately increases as the load pressure increases.…”
Section: Introductionmentioning
confidence: 99%